Beijing plus 10: An ambivalent record on gender justice - Maxine Molyneux; Shahra Razavi (United Nations Research Institute for Social Development (UNRISD), 2006)
The 1995 Fourth World Conference on Women (the 'Beijing Conference') was a landmark in policy terms, setting a global policy framework to advance gender equality. Ten years after Beijing, in March 2005, the UN's Commission on the Status of Women presided over an intergovernmental meeting in New York to review the progress achieved on the commitments made in the Beijing Declaration and Platform for Action. This 'Plus 10' event was decidedly low key. Its aim was not agenda setting but agenda confirming; not policy formulation, but policy affirmation. Whether it proves to be part of an ongoing worldwide movement in support of gender equality, or whether it marks the decline of that process, is a question that many in international women's movements are asking. This paper, drawing on research undertaken for the UNRISD report, Gender Equality: Striving for Justice in an Unequal World, reflects on the ambivalent record of progress achieved by women over the last decades and considers how the policy environment has changed over the period since the high point of the global women's movements. Drawing on a number of commonly employed indicators of 'women's progress', the paper argues that the record of achievement regarding gender equality is more ambivalent, and the causal influences more diverse and less unidirectional than is sometimes assumed. It also argues that development policies have an important role to play in securing outcomes, and that the first phase of the structural reforms (dating from the early 1980s) was in many respects negative for women. In the ten years since the Beijing Conference there have been some significant shifts in international development policy along with a growing appreciation of the need to develop gender aware policies. By the end of the 1980s, 'market fundamentalism' and shock therapy had lost much of their appeal, opening up a space for new ideas and approaches in development policy and practice. Growing discontent over the social effects of the reforms, as well as criticism from leading economists in the international financial institutions (IFIs) have brought about a policy shift, which is sometimes referred to as the 'Post-Washington Consensus'...
Keywords: 330